Influence of Si Content on Microstructure and Mechanical Properties of CoCrFeNi High-Entropy Alloys - Yajun Zhou; Ruifeng Zhao; Bo Ren; Aiyun Jiang; Zhongxia Liu; Jianxiu Liu (Metals)
CoCrFeNiSix (where x = 0, 0.5, 1.0, 1.5, 2.0 mol, named as H4, Si0.5, Si1.0, Si1.5, and Si2.0, respectively) high-entropy alloys (HEAs) were fabricated via hot-press sintering. The effects of Si content on the phase structure, microstructure, and mechanical properties of HEAs were investigated. The results show that the H4 alloy consists of a single FCC phase. As the Si content increases, the phases of CoCrFeNiSix HEAs transform from the FCC phase to the BCC and silicide phases. An increase in Si content can significantly enhance the hardness and yield strength of the alloys, yet at the expense of their plasticity. When the Si content increases from 0 to 2.0 mol, the hardness of the alloy increases from 280 HV to 1060 HV, the yield strength rises from 760 MPa to 1640 MPa, and the fracture strain drops to 6%. The strengthening mechanism of this HEA system mainly stems from the synergistic effect of solid solution strengthening and precipitation strengthening of silicide phases.